Niewydolność serca i płuc, transplantologiaExperience of the Department of Lung Diseases and Tuberculosis in Zabrze and the Silesian Centre for Heart Disease in Zabrze in referring patients with irreversible lung injury for lung transplantation in 2006 - Jastrzębski, Dariusz; Wojarski, Jacek; Nowak, Jolanta; Iwiński, Janusz; Gumola, Anna; Przybylski, Roman; Poloński, Lech; Kozielski, Jerzy; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
The Department of Lung Diseases and Tuberculosis and the Silesian Centre for Heart Disease has been involved in referring patients with the end stage of lung diseases for lung transplantation since 1999. In this paper we present the results of our study. We took into consideration the number of performed transplantations, time from referral to the transplantations, mean time of survival after transplantation and mean survival time in the waiting list. Special account was placed on principal diagnosis, risk factors, lung function tests and main reasons for deferral and disqualification of our patients from lung transplantation.